ANALISIS RANTAI PASOK BENIH IKAN NILA DI BALAI BENIH IKAN (BBI) GENTENG - Mahardika, Distra Satria; Mufaidah , Iid; Annas, Azwar (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Tilapia (Oreochromis niloticus) is one of the freshwater fish that is widely cultivated. However, during the production and distribution process of seeds, many obstacles can occur, ranging from seed quality, pond management to distribution. Therefore, an analysis of the tilapia seed supply chain is needed to determine the problems in the tilapia seed supply chain. This study aims to determine the conditions and problems in the tilapia seed supply chain at the Genteng Fish Seed Center (BBI). Supply chain analysis is carried out on every activity carried out during fish seed production from upstream to downstream. This study was conducted at the Genteng Fish Seed Center (BBI). The selection of locations and respondents was carried out using purposive sampling techniques based on the consideration that the Genteng Fish Seed Center (BBI) is one of the technical implementing units under the Banyuwangi Regency Fisheries Service which actively produces and distributes tilapia seeds to farmers in the Banyuwangi area and its surroundings. The research method used is a descriptive analysis method to determine the process and activities of the supply chain. Based on the analysis, it was found that the condition of the tilapia seed supply chain was good, but there were still several obstacles faced.